Akseptasi Program MBG di SDI Gere dalam Lensa Hak Individu Ockham (Pusat Riset dan Inovasi Nasional, 2026)
This study explores the acceptance of the Free Nutritious Meal Program (MBG) at SD Inpres Gere through William of Ockham's negative rights framework, focusing on freedom from external interference. As a positive rights policy (the right to services), the MBG has the potential to conflict with the principles of individual subjective rights (negative rights). Ockham emphasized that every individual has a personal sovereignty that must be free from interference from external authorities. Using qualitative research methods through literature studies and interviews, this article analyzes the risk of standardizing consumption that can reduce individual autonomy in determining their private needs. The analysis shows that although the MBG has a noble aim to fulfill the right to life, its implementation risks becoming a form of state paternalism that harms citizens' negative freedoms if not accompanied by strict limits on power. This paper concludes that to align with Ockham's principle of individual subjective rights, the MBG program must continue to respect the private space and diversity of individual choices without creating dependency that erodes the sovereignty of legal subjects.